Gender mainstreaming in the policy of islamic boarding school education: A systematic literature review - Asnal Mala; Uswatun Chasanah; Siti Marpuah (An-Nisa’ Journal of Gender Studies, 2025)
Although Islamic boarding schools (pesantren) are formally recognized within the national education system, the Pesantren Law lacks a specific gender-responsive legal framework. Consequently, male domination, policies without measurable indicators, and low gender literacy continue to perpetuate systemic inequality. This study analyzes the structural, cultural, and regulatory barriers to gender mainstreaming in pesantren, including male domination, normative policies, low gender literacy, the absence of a gender-responsive legal framework in the Pesantren Law, and weak monitoring mechanisms. This study employed a qualitative approach using a systematic literature review (SLR) method based on data from Publish or Perish, ERIC, and Google Scholar databases from 2013–2023. Thematic analysis was conducted using NVivo, while the PRISMA framework ensured validity and reliability. This study identified three findings: (1) gender mainstreaming in pesantren is hindered by male domination, normative policies, low literacy, and no gender framework in the Pesantren Law; (2) the Law lacks indicators and monitoring, so male domination in leadership and curriculum persists; (3) male leadership and conservative interpretations impede equality, demanding curriculum reform, inclusive policies, and women’s empowerment. This study concludes that gender mainstreaming in pesantren remains stagnant due to male domination, policies lacking measurable indicators, and weak regulatory frameworks, thereby making structural reform an urgent necessity. This study contributes to expanding the theory of power relations in education while offering substantive and accountable gender policy reforms in pesantren.